REASSESSING THE ZIMBABWEAN CHIPENDANI (Article withdrawn) - Kyker, Jennifer W. (International Library of African Music, 2016)
Due to an error in the original publication this article will be reprinted in the 2018 edition of African Music. We apologise for any inconvenience. (Editor: African Music)
Keywords: Chipendani; Shona (African people); Musical bow; Ritual; Zimbabwe; African Music